Microbial champions: The influence of gut microbiota on athletic performance via the gut-brain axis - Xia, W.; Li, X.; Han, R.; Liu, X. (Open Access Journal of Sports Medicine, 2024)
Abstract: In recent years, exercise has shown a powerful ability to regulate the gut microbiota received with concern. For instance, compared with the sedentary group, high-level athletes showed a different gut microbiota composition and remarkable capability of physiological metabolism. In addition, different diet patterns (eg, high-fat diet, high carbohydrate diet et.al) have different effects on gut microbiota, which can also affect exercise performance. Furthermore, adaptations to exercise also might be influenced by the gut microbiota, due to its important role in the transformation and expenditure of energy obtained from the diet. Therefore, appropriate dietary supplementation is important during exercise. And exploring the mechanisms by which dietary supplements affect exercise performance by modulating gut microbiota is of considerable interest to athletes wishing to achieve health and athletic performance. In this narrative review, the relationship between gut microbiota, dietary supplements, training adaptations and performance is discussed as follows. (i) The effects of the three main nutritional supplements on gut microbiota and athlete fitness. (ii) Strategies for dietary supplements and how they exerted function through gut microbiota alteration based on the gut-brain axis. (iii) Why dietary supplement interventions on gut microbiota should be tailored to different types of exercise. Our work integrates these factors to elucidate how specific nutritional supplements can modulate gut microbiota composition and, consequently, influence training adaptations and performance outcomes, unlike previous literature that often focuses solely on the effects of exercise or diet independently. And provides a comprehensive framework for athletes seeking to optimize their health and performance through a microbiota-centric approach.